Axial buckling of imperfect cylindrical steel silos with isotropic walls under stored solids loads: FE analyses versus Eurocode provisions. (July 2022) - Mehretehran, Alireza Moazezi; Maleki, Shervin
Graphical abstract: Highlights: Axial buckling of imperfect isotropic steel silos under stored solids loads were investigated. Elaborations on the Eurocode buckling stress design procedure were given. Comprehensive Finite Element (FE) analyses of imperfect silos were performed. Weld-induced and eigenmode-based imperfections were included in the analyses. Relevant Eurocode provisions were examined against FE analyses. Abstract: Stored solids loads on silo vertical walls are composed of two orthogonal components: the horizontal component that internally pressurizes the silo and the vertical wall frictional component that causes axial compression. For an imperfect cylinder, the elastic axial buckling resistance may be considerably raised by a uniform internal pressure as it alleviates the detrimental effect of the geometrical imperfections. However, at high internal pressures, the combination of axial compression and circumferential tension may result into a plastic instability that is commonly termed elephant's foot buckling. Both stabilizing and destabilizing effects of internal pressure are taken into account by EN 1993–4-1 in the buckling stress design of steel silos with isotropic walls under axial compression. In this paper, using non-linear Finite Element (FE) analyses, the effects of internal pressure on axial buckling of steel silos have been fully investigated and the Eurocode provisions on this issue have been thoroughly examined.